MINIMAL RESIDUAL DISEASE ASSESMENT IN PATIENTS WITH ACUTE MYELOID LEUKEMIA BY MULTICOLOUR FLOW CYTOMETRY (LITERATURE REVIEW) - T. I. Lobanova; I. V. Galtseva; E. N. Parovichnikova (Онкогематология)
Patients with acute myeloid leukemia (AML) have a high risk of relapse. Determination of the presence of residual tumor cells during the remission of AML allows predicting the onset of relapse. Slow decrease of blast cells after induction courses is associated with a high probability of relapse. There are two most sensitive methods for determining minimal residual disease (MRD): molecular (polymerase chain reaction – PCR, droplet digital PCR, next generation sequencing – NGS) and immunophenotypic (multicolor flow cytometry – MFC). Both methods have advantages and disadvantages. The molecular diagnostic method is more sensitive, but it takes more time to get the result (from several days). Measurement of MRD by PCR is applicable in 40–50 % of AML patients, and by MFC – in 90 % of patients. The MFC method is based on the identification of antigens combination that is characteristic of tumor cells and is not found on normal hematopoietic cells. There are several drawbacks of the MFC method: the change of tumor clone immunophenotype during treatment, the inadequate difference in the antigen profiles of tumor cells and normal cells, difficulties in evaluating the MRD status in low cellularity bone marrow or blood sample. In AML patients the effect of MRD, measured by the MFC method, on long-term treatment outcomes was well-demonstrated. Evaluation of early MRD status shows tumor chemosensitivity and therapy efficacy. Despite the different approaches in MRD detection, thresholds and the combination of monoclonal antibodies, the lack of standardization, “positive” MRD values in early or later stages of therapy worsen the disease-free (DFS) and overall survival (OS) in AML patients. So far, the principles of MRD-directed therapy have not been developed, but protocols exist with the use of targeted drugs in combination with standard chemotherapy that help to reduce the MRD level. It is proved that the intensification of treatment does not affect the quantitative value of MRD and the long-term results of therapy. New prospective studies are needed to search for universal MRD markers, to create a standardized panel of monoclonal antibodies and to develop a specific therapy strategy in accordance with the MRD values.